Overlapping assistance distribution of the Indonesian government’s scheme for small and micro-scale enterprises during COVID-19 - Tusianti, Ema; Abdurrahman, Abdurrahman; Simanjuntak, Tigor Nirman (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
The Indonesian Government introduced a financial government scheme called Bantuan Produktif Usaha Mikro (the BPUM) to protect and support the operations of small and microscale enterprises (SMEs) during the difficulties of the COVID-19 pandemic. This study describes the BPUM distribution based on the characteristics of its recipients. Using the 2021 National Socioeconomic Survey and the binary logistic regression method, it is found that BPUM tends to be allocated to recipients with levels of education below university level, who are male, have access to the internet, and live in urban areas. Surprisingly, the BPUM is also distributed to the beneficiaries accessing microfinance, such as People’s Business Credit (Kredit Usaha Rakyat, KUR). However, those beneficiaries are not supposed to be the scheme’s recipients. This situation indicates that BPUM is not being accurately distributed. In contrast, the BPUM is also distributed to households that receive several social protection programs simultaneously, including those from the State Budget, Local Government Budget, and Special Autonomy Funds (Otsus) at the local level. Furthermore, the study reveals issues with data integration and highlights inefficiencies in budget allocation. These findings serve as valuable insights for program evaluation, aiming to enhance the allocation of BPUM or another similar program to rightful recipients and increase its effectiveness in supporting SMEs.